(untitled) (Training and Practice : Journal of Educational Sciences, 2023)
Research on the effects of parental involvement in their children’s education in school settings has shown that more active parental involvement in school life to support children’s learning has a positive impact on academic achievement and student integration, and that family-school relationships and cooperation also play an important role in children’s education. School-parent cooperation is also present in public schools, but alternative schools and co-educational schools expect more decisive and active involvement from parents than mainstream schools. The forms and intensity of the expected cooperation vary between alternative schools and learning communities, and this study aims to provide a picture of the forms, possible areas and extent of parental involvement expected in alternative schools and learning communities.